ANALYSIS OF CUSTOMER SATISFACTION USING THE CUSTOMER SATISFACTION INDEX (CSI) METHOD AT YOURLIGIE SALON SMK 6 SURABAYA: ANALISIS KEPUASAN PELANGGAN DENGAN METODE CUSTOMER SATISFACTION INDEX ( CSI ) PADA YOURLIGIE SALON SMK 6 SURABAYA - Yona Okatafariska Sulu; Mutimmatul Faidah; Sri Usodoningtyas; Octaverina Kecvara Pritasari (Jurnal Tata Rias, 2025)
Abstract The main issue identified yourlige salon is the decline in the number of customers, which affects the salon's revenue and operational stability. This study aims to analyze customer satisfaction levels at Yourligie Salon SMK 6 Surabaya using the Customer Satisfaction Index (CSI) method. The research employs a quantitative approach with a survey design, where data is collected through questionnaires distributed to salon customers. The analysis is conducted using CSI calculations to measure customer satisfaction regarding tangible aspects, reliability, assurance, responsiveness, and empathy. The results indicate that the customer satisfaction level is 76.59%, suggesting that customers are satisfied with the services provided. The most satisfying aspects include product quality, facility comfort, and staff professionalism, while deficiencies were found in employee skills and facility completeness. In conclusion, although the salon's services are considered good, improvements are still needed in staff training and facility enhancement. Keywords: customer satisfaction, customer satisfaction index (CSI).